The Italian National Antarctic Museum (MNA, Section of Genoa): a national heritage and a scientific resource for the study of Antarctic biological samples : Italian National Antarctic Museum - Genoa - Schiaparelli, Stefano; Alvaro, Maria Chiara; Carbone, Cristina; Cecchetto, Matteo; Belmonte, Donato; Guzzi, Alice (Medicina Historica, 2020)
The Italian National Antarctic Museum (MNA, www.mna.it) was established in 1996 with the aim of preserving the collections of Antarctic organisms, geological samples and ice samples that are acquired each year in the framework of the Antarctic expeditions of the Italian National Antarctic Program (PNRA). Beginning with the first Italian Antarctic expedition held in 1985, thousands of museum vouchers have been progressively acquired by MNA, now representing a valuable Italian heritage. The structure of the MNA is that of a consortium formed by the Universities of Genoa, Siena and Trieste, each one dedicated to different researches and activities: biology and ecology (Genoa), Earth sciences (Siena), history of Antarctic exploration and marine geology (Trieste). There are also seven Associated Sections that ensure the maintenance of specific collections, such as those of cultured organisms and ice cores, which require specific conservation conditions and study protocols. With the aim of increasing outreach activities and stimulate curiosity about the unique Antarctic living forms, the MNA has established a gallery of 3D models realized by using photogrammetric techniques. The MNA collaborates with the Barcode of Life consortium in order to better characterize the determinations of the species in its collections and share barcodes with the whole scientific community. Overall, in the past five years, the MNA was able to establish a variety of collaborations at the international level, gaining support of leading scientist and participating to initiatives at the international level.